De'5 Pastry-Licious - Azni, Nurfatehah; Dua, Veronika; Jm Gining, Viveca Jusnney; Kennedy, Dyg Nurhazlinie; Pijuntung, Mulini (2014)
We are starting our own business as partners and deciding to call our business as De'5 Pastry-Licious. Our main activity of business is selling pastry especially cakes. Our shop is not only focus on cheese crepe cake but other pastry product such as biscuit and beverages. There are several important departments to run our business smoothly, which are administrative department, marketing department, operational department and financial department. Each of us will head one of the departments while there will be one person acts as General Manager, who will be the head of all the departments in our business. We started this business by applying loan where each of our partners been approved for loan with the amount of RM 12,773. Our office located in our shop lot so that it will easy for us while working. It is located at Lintas Plaza, Kota Kinabalu, Sabah. We chose this location because it is the centre of attraction during days and night. So, we are trying the opportunity to get and attract the customer here.